Impactos da pandemia de COVID-19 nas exportações do setor moveleiro de Bento Gonçalves - Schmitz, Priscila Stail (My University, 2021)
Humanity has been challenged since its beginning, either by political and economic disputes or by threats from viruses and bacteria that have plagued it throughout its history. Such challenges reflect how society is today. Since the emergence of the coronavirus in December 2019, many lives have been lost, social and economic conditions have worsened worldwide, especially in Brazil, where sectors and markets have been affected. In view of the factual reality experienced, it is relevant to understand how the furniture sector in Bento Gonçalves region is facing such pandemic scenario regarding to the exports. In this context, the present study aims to identify and analyse the main impacts on exports of the furniture sector in the named area as a result of the COVID-19 pandemic, which can serve as a future learning on how the sector faced the challenges from 2020, in addition to obstacles it is still facing. In order to accomplish this objective, both quantitative and qualitative methodologies were applied, respectively in exploratory and descriptive levels, through case study and survey strategies. Based on the collected data and its proper analysis, the results confirm that several challenges and difficulties were faced by the sector in the first months after the onset of the disease, given the measures imposed to fight against it. However, at the same time, it was found that the sector managed to transform this unique moment in an opportunity for innovation and there are indicators of its gradual recovering. [resumo fornecido pelo autor]
A humanidade vem sendo desafiada desde seus primórdios, seja por disputas políticas e econômicas ou por ameaças de vírus e bactérias que a acometem ao longo da história. Tais desafios refletem em como a sociedade se encontra atualmente. Desde o surgimento do coronavírus, em dezembro de 2019, perdeu-se muitas vidas, houve agravamento das condições sociais e econômicas no mundo e, em especial no Brasil, onde setores e mercados foram atingidos. À vista da factual realidade vivenciada, é pertinente o entendimento de como o setor moveleiro da região de Bento Gonçalves está enfrentando tal cenário pandêmico em relação às exportações. Nesse contexto, o presente estudo busca identificar e analisar os principais impactos nas exportações do setor moveleiro da região de Bento Gonçalves em decorrência da pandemia de COVID-19, sendo este, um estudo que poderá servir como futuro aprendizado em como o setor encarou os desafios a partir de 2020, além dos obstáculos que o mesmo ainda está enfrentando. A fim de atingir esse objetivo, empregou-se procedimentos metodológicos qualitativos e quantitativos, respectivamente aplicando-se níveis exploratório e descritivo, por meio de estratégias de estudo de caso e survey. A partir dos dados obtidos e de sua devida análise, os resultados confirmam diversos desafios e dificuldades enfrentadas pelo setor nos primeiros meses após o surgimento da doença, dadas as medidas impostas para seu combate, porém, ao mesmo tempo, verificou-se que o setor conseguiu fazer desse momento uma oportunidade para inovações e se recupera gradativamente. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Indústria de móveis - Bento Gonçalves (RS); Exportação; Pandemias; Coronavírus